2020
DOI: 10.1038/s41598-020-76863-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase intrinsically regulates glucose sensing and glucagon secretion in pancreatic alpha cells

Abstract: The secretion of glucagon by pancreatic alpha cells is regulated by a number of external and intrinsic factors. While the electrophysiological processes linking a lowering of glucose concentrations to an increased glucagon release are well characterized, the evidence for the identity and function of the glucose sensor is still incomplete. In the present study we aimed to address two unsolved problems: (1) do individual alpha cells have the intrinsic capability to regulate glucagon secretion by glucose, and (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…Remarkably, the entire set of glycolysis genes, from GCK to PDH is downregulated in alpha cells from GADA+ donors. It was recently demonstrated that the rate of glycolytic flux via glucokinase and thus ATP production determines the setpoint for inhibition of glucagon secretion by glucose (Bahl et al, 2021; Basco et al, 2018; Moede et al, 2020). Therefore, if GADA+ alpha cells produce ATP from glucose less efficiently because of lower glycolytic flux and oxidative phosphorylation, then a given concentration of glucose would less efficiently suppress glucagon secretion, providing a possible molecular explanation for the physiological observations shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the entire set of glycolysis genes, from GCK to PDH is downregulated in alpha cells from GADA+ donors. It was recently demonstrated that the rate of glycolytic flux via glucokinase and thus ATP production determines the setpoint for inhibition of glucagon secretion by glucose (Bahl et al, 2021; Basco et al, 2018; Moede et al, 2020). Therefore, if GADA+ alpha cells produce ATP from glucose less efficiently because of lower glycolytic flux and oxidative phosphorylation, then a given concentration of glucose would less efficiently suppress glucagon secretion, providing a possible molecular explanation for the physiological observations shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Glucagon secretion from alpha cells is impacted by cAMP (Yu et al, 2019) and Ca 2+ (Vieira et al, 2007), as well as intra-islet insulin (Xu et al, 2006), GABA (Kittler and Moss, 2003; Xu et al, 2006), cAMP-activated ion channels (Huang et al, 2017), and gap junctions (Dufer, 2018). A direct role for glucose sensing via glucokinase in alpha cells has also been identified as a key factor in glucose inhibition of glucagon secretion (Bahl et al, 2021; Basco et al, 2018; Moede et al, 2020). In addition, glucagon released from alpha cells acts in a paracrine fashion on beta cells, with this crosstalk important for high efficiency glucose stimulation of insulin secretion (Sharma et al, 2018; Svendsen et al, 2018; Zhu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Much debate has centered around the question of whether glucose-suppression of glucagon secretion is mediated via intrinsic, paracrine, or autonomic mechanisms although it seems likely that acells (like b-cells) adeptly integrate multiple signals for precise physiologic control of glucagon. A role for direct glucose-sensing in the a-cell is supported by the impact of cell-specific glucokinase knockout (Basco et al, 2018), the effect of glucokinase activation or knockdown on exocytosis from a-cells (Moede et al, 2020) and in vivo glucagon responses (Bahl et al, 2021), and the ability of glucose metabolism to modulate a-cell ATP-sensitive K + channels (Zhang et al, 2013) among other cell-autonomous effects (Gylfe, 2016). Here we show that increasing glucose suppresses exocytosis from human and mouse acells stimulated by direct membrane depolarization, consistent with a recent report in human a-cells where exocytosis was measured by live-cell imaging (Omar-Hmeadi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] In the liver, glucokinase processes glucose after a meal and converts it into glycogen in a glucose-dependent manner. [ 1 ] Therefore, the enzyme functions as a glucose sensor in pancreatic β-cells. In normal physiological states, the blood glucose level is maintained between 3.9 and 5.6 mmol/L (homeostasis) to ensure that the brain, red blood cells, and other glucose dependent cells remain in a healthy state.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, glucokinase has a central role in glucose homoeostasis, with the blood glucose levels being maintained at 4 to 6.5 mmol/L. [ 1 ] The mutation of the human glucokinase gene causes a decrease in glucokinase activity in β-cells and thus an increase in the threshold of blood glucose, which leads to moderate fasting hyperglycemia in young patients with maturity-onset diabetes. [ 2 ] It has been clinically demonstrated that impaired glucokinase function can cause glucose metabolic diseases, including type 2 diabetes mellitus (T2DM).…”
Section: Introductionmentioning
confidence: 99%